Key paediatric messages from Amsterdam. Issue 2 (29th April 2016) - Grigg, Jonathan; Barben, Jürg; Bohlin, Kajsa; Everard, Mark L.; Hall, Graham; Pijnenburg, Mariëlle; Priftis, Kostas N.; Rusconi, Franca; Midulla, Fabio
The Paediatric Assembly of the European Respiratory Society (ERS) maintained its high profile at the 2015 ERS International Congress in Amsterdam. There were symposia on preschool wheeze, respiratory sounds and cystic fibrosis; an educational skills workshop on paediatric respiratory resuscitation; a hot topic session on risk factors and early origins of respiratory diseases; a meet the expert session on paediatric lung function test reference values; and the annual paediatric grand round. In this report the Chairs of the Paediatric Assembly's Groups highlight the key messages from the abstracts presented at the Congress. Paediatric highlights of the 2015 ERS International Congress http://ow.ly/10iBsz